Keyakinan Beriman Kepada Hari Akhir Dalam Perspektif Islam - Hanifah Dzakirah; Nurul Fadhilah; Hayatul Falah; Lisa Lisa; Wismanto Wismanto (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This research discusses the belief in the Last Day from an Islamic perspective, which is one of the important pillars of faith. The background of this research is based on the importance of understanding the Last Days in shaping the behavior and morals of Muslims. The aim of the research is to explore how belief in the Last Day affects the daily lives of Muslims in spiritual and social aspects. The research method used is qualitative with a literature study approach, analyzing various sources of religious texts and related Islamic literature. The research results show that belief in the Last Day encourages Muslims to increase morality, justice and social responsibility, as well as providing a deep understanding of divine justice and life after death.